Development of Arabic Teaching Materials Based on Google Classroom - Adam Mudinillah; Xie Guilin; Deng Jiao (International Journal of Educational Narratives, 2023)
Background. Based on the problems obtained by researchers about the problem of Arabic language in Indonesia at this time is very minimal, because there are elements that inhibit the implementation of Arabic language learning. Among them, namely, kitabah, kalam, istima', thus the process of learning Arabic in school development is very lacking. Purpose. Thus, researchers have a goal of learning Arabic through google clasrooom to make it easier for students to carry out Arabic language learning more effectively and efficiently. And how influential is Arabic language learning using google meet media when used for student learning activities, and the subject of researchers conducted at the madrasa ibtidaiyah teluk kuantan to find out the Arabic language learning process using google meet media to what extent the effectiveness of learning media google meet application. Method. And this type of research uses quantitative data, the object of which is carried out by researchers there are students from madrasah ibtidaiyah teluk kuantan. And the data collection technique used is interviews. The results of the study aim to help students and teachers at madrasah ibtidaiyah teluk kuantan be able to apply Arabic language learning using the google classrom application media and can motivate students to learn in using the google meet application media. Results. The result of the study aims to help students and teachers at the madrasa ibtidaiyah teluk kuantan be able to apply Arabic language learning by using the google classrom application media and can motivate students to learn in using the google meet application media. Then the results of the questionnaire data obtained by researchers know the use of google meet media and what Arabic language learning is used by teachers and students at madrasah ibtidaiyah teluk kuantan. Conclusion. And researchers hope that with the use of the google meet application media for Arabic language learning and other learning can be applied by teachers and students so that there is an effective and efficient learning process.